Aktivitas Antibakteri dan Toksisitas Teripang Stichopus sp. - Rasyid, Abdullah (Indonesian Research Gateway)
Sea cucumber Stichopus sp. is one of the marine life that has the potential to be developed as a source of antibacteriak agents. Research on the antibacterial activity and toxicity test of sea cucumber Stichopus sp. aims to determine the antibacterial activity and the toxicity level of sea cucumber Stichopus sp. extract against Artemia salina. The method used for antibacterial activity test was the agar diffusion method, while toxicity tests using the Brine Shrimp Lethality Test (BSLT). The result showed that the extract of sea cucumber Stichopus sp. has antibacterial activity against Staphylococcus aureus, Bacillus subtilis and Vibrio eltor. Extracts of sea cucumber Stichopus sp. are active against BSLT test marked with LC50 values of less than 1000 ppmKeywords : Sticopus sp., antibacterial activity, toxicity test.